2012
DOI: 10.1002/ps.3433
|View full text |Cite
|
Sign up to set email alerts
|

A rapid diagnostic technique of Bactrocera cucurbitae and Bactrocera zonata (Diptera: Tephritidae) for quarantine application

Abstract: Backround The melon fruit fly Bactrocera cucurbitae and the peach fruit fly Bactrocera zonata are serious pests, native to Asia, that have recently invaded Egypt. In Tunisia, no report of these species has yet been made, but pest risk data suggest that both Bactrocera species are likely to establish in other countries of the Mediterranean region. Results A quick method, based on a PCR‐RFLP of the mitochondrial COI gene, has been developed to enhance species identification for quarantine purposes. The restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Chua et al (2010) showed that this molecular method is effective even when only body parts or immature stages of tephritid fruit flies are present. Khemakhem et al (2012) successfully developed PCR-RFLP patterns of the COI gene in Tunisia to reliably identify and separate the quarantine pests B.curcubitae, B. zonata and C.capitata.…”
Section: Discussionmentioning
confidence: 99%
“…Chua et al (2010) showed that this molecular method is effective even when only body parts or immature stages of tephritid fruit flies are present. Khemakhem et al (2012) successfully developed PCR-RFLP patterns of the COI gene in Tunisia to reliably identify and separate the quarantine pests B.curcubitae, B. zonata and C.capitata.…”
Section: Discussionmentioning
confidence: 99%
“…To authenticate the studied Bruchus species, we sequenced their DNA barcode region (COI). The COI mitochondrial DNA region was amplified for all samples using the universal primers designed by Folmer et al [24], LCO-1490: 5´TTTCTACAAATCATA-AAGATATTGG3´ and HCO-2198 5'TGATTTTTT-GGTCACCCTGAAGTTTA3´, and PCR conditions described by Mezghani et al [25]. The full-length MLEs specific to the mauritiana subfamily were amplified by the degenerate Mos1 primer 5'TAYCAGGRGTA-CAAGTAKGRAA3' described by Kharrat et al [26].…”
Section: Pcr Amplificationmentioning
confidence: 99%
“…In recent decades, molecular biology techniques have been continuously explored for the identification of fruit flies. These techniques include AFLP (amplified fragment length polymorphism) (Kakouli-Duarte et al, 2001), RFLP (restriction fragment length polymorphism) (Chua et al 2010, Mezghani Khemakhem et al 2013), RAPD (random amplified polymorphic DNA) (Sonvico et al 1996, Zhang et al 2004), DNA barcoding techniques (Zhang et al 2019, Li et al 2022), species-specific PCR and qPCR techniques (Jiang et al 2016, Koohkanzade et al 2018, Zheng et al 2019), etc. These tools are generally cumbersome, require rather expensive equipment and setup, and are generally time consuming.…”
Section: Introductionmentioning
confidence: 99%